A global potential energy surface for H3+. (3rd July 2019) - Mizus, Irina I.; Polyansky, Oleg L.; McKemmish, Laura K.; Tennyson, Jonathan; Alijah, Alexander; Zobov, Nikolai F.
ABSTRACT: A globally correct potential energy surface (PES) for the H 3 + molecular ion is presented. The Born-Oppenheimer (BO) ab initio grid points of Pavanello et al. [ J. Chem. Phys. 136, 184303 (2012)] are refitted as BOPES75K, which reproduces the energies below dissociation with a root mean square deviation of 0.05 cm −1 ; points between dissociation and 75, 000 cm −1 are reproduced with the average accuracy of a few wavenumbers. The new PES75K+ potential combines BOPES75K with adiabatic, relativistic and quantum electrodynamics (QED) surfaces to provide the most accurate representation of the H 3 + global potential to date, overcoming the limitations on previous high accuracy H 3 + PESs near and above dissociation. PES75K+ can be used to provide predictions of bound rovibrational energy levels with an accuracy of approaching 0.1 cm −1 . Calculation of rovibrational energy levels within PES75K+ suggests that the non-adiabatic correction remains a limiting factor. The PES is also constructed to give the correct asymptotic limit making it suitable for use in studies of the H + + H 2 prototypical chemical reaction. An improved dissociation energy for H 3 + is derived as D 0 = 35, 076 ± 2 cm −1 . GRAPHICAL ABSTRACT: